1972
DOI: 10.1530/acta.0.0710226
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Change in Hypothalamic Lactic Dehydrogenase Activity in the Adult Female Rat

Abstract: Lactic dehydrogenase (LDH) activity in the anterior, middle and posterior hypothalamus has been studied in adult female rats during the different phases of the oestrous cycle. Differences in LDH activity were found in the middle and posterior hypothalamus. LDH activity in the middle hypothalamus was significantly higher between 5:30 a. m. and 7:00 a. m. on the day of pro-oestrus than during the other phases (P < 0.01). (Rats were exposed to a controlled light schedule of 12 hours of light daily from 10 p. m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1978
1978
1986
1986

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Such variations are similar to those reported about oxygen uptake [Moguilevsky et al, 1968;Schiaffini et al, 1969;Schiaffini et al, 1970;Schiaffini and Marin, 1971] and C 0 2 production from labelled glu cose [Scacchi et al, 1973], and agree well with the changes in total LDH activity of the HYP found by Morishita et al [1972].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Such variations are similar to those reported about oxygen uptake [Moguilevsky et al, 1968;Schiaffini et al, 1969;Schiaffini et al, 1970;Schiaffini and Marin, 1971] and C 0 2 production from labelled glu cose [Scacchi et al, 1973], and agree well with the changes in total LDH activity of the HYP found by Morishita et al [1972].…”
Section: Discussionsupporting
confidence: 90%
“…One of these changing enzymes is lac tate dehydrogenase (LDH) [Morishita et al, 1972;Packman et al, 1976]. However, little Received: February 22, 1978 Accepted after revision: August 16, 1978 attention has been paid to the nature of LDH present in the HYP: LDH in most tissues is a tetrameric molecule composed of 2 types of subunits (A or M and B or H) that are able to combine into the 5 molecular form s-iso enzymes (ISO) -of LDH [Cahn et al, 1962;Goodfriend and Kaplan, 1964], Since the A/B subunits ratio of LDH extracted from such estrogen target tissues as human endometrium [.Spellman and Fottrell, 1972], rat uterus and anterior pituitary (PIT) Anda et al, 1976b] seems to be dependent on the levels of these hormones, it was considered of interest to study the LDH…”
mentioning
confidence: 99%
“…The stages of the 4-day estrous cycle are defined as estrus, 2 days of diestrus and proestrus. Under the conditions of our laboratory, the critical period is between 5.00 and 8.00 h on the day of proestrus [6], and the time of ovulation is confirmed to be between 18.00 and 21.00 h in the early period of the day following proestrus. The results were statistically evaluated by Student's t test.…”
Section: Animalsmentioning
confidence: 62%
“…Animals were exsanguinated. The brain was immediately removed from the cranium, and the anterior hypothalamus was dissected out as a block of tissue, according to the limits described by Morishita et al [7], and was stored at -2 0 °C until assayed. Only the tissue of the anterior hypothalamus taken at 5.00-6.00 h on the day of proestrus was weighed on an ana lytical balance.…”
Section: Treatment O F Animalsmentioning
confidence: 99%